The Effectiveness of Assertive Communication Training in Improving Teachers' Capacity to Prevent Sexual Violence and Bullying in Elementary Schools - Kurniaman, Otang; Noviana, Eddy; Novianti, Ria; Permana, Dede; Linda, Roza; Sari, Intan Kartika; Al Fajar, Beny; Radini, Radini; Putra, Rezi Andesta; Alifarani, Afra (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Background: This community service program aimed to prevent sexual violence and bullying through assertive communication training for elementary school teachers in Maredan Barat Village, Tualang District, Siak Regency. Teachers, as strategic actors in creating a safe school environment, often face limitations in understanding and skills when handling cases of sexual violence and bullying.Aims: To improve teachers' understanding, skills, and attitudes towards sexual violence and bullying in the school environment.Methods: The training, conducted from June to October 2024, was designed to enhance teachers’ understanding, skills, and attitudes by integrating the local Riau Malay culture. The program involved 40 teachers from several schools in the village. The training was carried out in three stages: socialization to provide basic understanding, simulation, and role-play to improve assertive communication skills, and evaluated using pretest and posttest questionnaires.Results: The evaluation results showed significant improvements in all indicators. In preventing sexual violence, the average score for understanding increased from 3.12 to 4.45, assertive communication skills from 1.97 to 4.32, and attitudes toward prevention from 3.23 to 4.47. In preventing bullying, the average understanding score rose from 3.21 to 4.57, communication skills from 2.12 to 4.47, and attitudes from 3.13 to 4.68. These improvements demonstrate the effectiveness of the training in equipping teachers with better assertive communication techniques, strengthening their understanding, and transforming their attitudes to be more proactive and responsible.Conclusion: This program has proven successful in enhancing teachers’ capacity to prevent sexual violence and bullying, making them more prepared and confident in addressing these issues.